Penyuluhan Pengolahan Sampah Rumah Tangga Menjadi Stool untuk Ibu-Ibu PKK di Kalurahan Srimulyo - Wahyu Eka Priana Sukmawaty; Ilya Khoerus Sholihah (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Household waste processing is still a challenge. Various ways have been done so that household waste has more value and is more useful. One way is done through counseling. This counselling aims to improve the knowledge, understanding, and skills of PKK mothers in household waste management. Thus, it is expected to be able to change the pattern of behaviour and household habits towards more sustainable and environmentally friendly practices. Counselling was carried out to PKK mothers in Kalurahan Srimulyo Piyungan Bantul. The counselling activity will be held on December 22, 2023, in the multipurpose room/hall of Kalurahan Srimulyo Piyungan Bantul. The extension activities carried out include the presentation of material related to waste processing in general starting from recycling, the waste hierarchy process (consisting of reduce, reuse, and recycling along with examples of activities), and then material related to stools/chairs from RT waste in the form of used plastic bottles and used clothes. This waste processing extension activity is the beginning of activities before entering the practical stage for the process of making stools from used plastic bottles and used clothes.